Factors Affect Green Food Consumption Intention of Consumers in Hanoi - Thoa, Hoang Thi Bao; Kien, Hoang Le; Uyen, Nguyen Thu; Uyen, Nguyen Thi (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2019)
Green consumption has become an important academic and practical topic however green food consumption is a quite new concept with many consumers in Hanoi. Taking the cognitive view in studying consumer behaviors, this study theoretically developed and tested factors that affect green food consumption intention and behavior of consumers in Hanoi, namely Attitude towards the environment, Attitude towards green food consumption, Subjective norm of green consumption, Perceived consumer effectiveness and belief. Our data sample of 260 consumers in Hanoi provided supports for the hypotheses. Our study results thus contribute to the green consumption literature and the broader literature of consumer behavior. Implications and recommendations for further research are also discussed.